REVIEW OF LANGALI (GLORIOSA SUPERBA LINN) – AGADA TANTRA PERSPECTIVE - C.M, *ATHULYA; P, NEETHU; VIJAYAN, VIJITHA; RAJESH, ARATHI (International Journal of Ayurveda and Pharma Research, 2019)
Agadatantra is a branch of Ayurveda which deals with the symptoms and treatment of various animal, plant, artificial and latent poisons. The drug Langali (Gloriosa superb Linn) is being categorized under Moolavisha (poisonous roots) and is also one among the nine Upavishas (semi poisonous drugs) by different Ayurvedic pharmacopoeias. Even though it is poisonous it has got Shothahara (anti-inflammatory), Vranahara (wound healing), Krimigna (wormicidal), Shalyaharana (removal of foreign substances), Garbapaatana (abortificant) properties etc. It is being used by the Ayurvedic physicians in treatment of various ailments after proper purification. But its purificatory methods are not mentioned in Samhitas (treatises). It is mentioned in Ayurveda prakasha and traditional Agadatantra text books of Kerala. Here in this article an attempt is made to collect the information regarding Langali in Agadatantra perspective. The article includes both modern and Ayurvedic concepts in regards to its symptoms during poisoning and its treatment. Details regarding its purificatory methods and its therapeutic use in compound formulations as an antidote which has been mentioned in the traditional Agadatantra books which are available in Kerala have also been included.